Alveolar macrophage phagocytosis is impaired in children with poorly controlled asthma - Fitzpatrick, Anne M. (2008)
BACKGROUND: Lower respiratory tract infection is a differentiating feature of children with poorly controlled asthma. Objective: Given the role of alveolar macrophages (AMs) in innate immunity, we hypothesized that AM phagocytosis might be impaired in poorly controlled asthma. METHODS: Bronchoalveolar lavage fluid AMs were isolated from 28 asthmatic children (moderate asthma, n = 12; severe asthma, n = 16), 10 nonasthmatic children with chronic cough treated with inhaled corticosteroids, and 10 healthy adult control subjects. AMs were stimulated with LPS and exposed to fluorescein isothiocyanate–conjugated Staphylococcus aureus for 2 hours. Phagocytosis was quantified by using a phagocytic index (PI) calculated from the percentage of phagocytic cells multiplied by the relative fluorescence (RFU) units of S aureus per cell. Apoptosis was determined from the percentage of cells positive for poly (adenosine diphosphate–ribose) polymerase. RESULTS: Phagocytosis as measured by using the unstimulated PI was decreased in subjects with poorly controlled asthma (healthy control subjects, 9330 ± 3992 RFU; chronic cough, 9042 ± 5976 RFU; moderate asthma, 4361 ± 2536 RFU; severe asthma, 3153 ± 1886 RFU; P < .001) and remained unchanged with LPS stimulation. Children with severe asthma also had increased AM apoptosis, both the unstimulated and LPS-simulated states (P < .001), which correlated with the PI. CONCLUSIONS: AM function is compromised in children with poorly controlled asthma and is characterized by decreased phagocytosis and increased apoptosis.